Adrenergic regulation of conduction velocity in cultures of immature cardiomyocytes - de Boer, T.P. (Bohn Stafleu van Loghum, 2008)
During cardiac maturation, increased exposure of the heart to circulating catecholamines correlates with increased conduction velocity and growth of the heart. We used an in vitro approach to study the underlying mechanisms of adrenergic stimulation induced changes in conduction velocity. By combining functional measurements and molecular techniques, we were able to demonstrate that the increased conduction velocity after β-adrenergic stimulation is probably not caused by changes in intercellular coupling. Instead, RT-PCR experiments and action potential measurements have shown an increased excitability that may well explain the observed increase in conduction velocity. Apart from being relevant to cardiac maturation, our findings are relevant in the context of stem cells and cardiac repair. Preconditioning of stem cell derived cardiomyocytes may help to enhance electrical maturation of de novo generated cardiomyocytes and consequently reduce their proarrhythmogenic potential. (Neth Heart J 2008;16:106-9.)